Meteorus arizonensis Muesebeck, 1923 (Hymenoptera: Braconidae): nuevo registro para México - Gutiérrez-Ramírez, Antonio; Robles Bermúdez, A.; Cambero-Campos, J.; Coronado-Blanco, J. M. (Instituto de Ecología, A.C., 2015)
Braconidae is one of the more diverse families of Hymenoptera with almost 20,000 species worldwide. Meteorus has 316 species and is almost cosmopolitan. Previously, seven species of this genus have been recorded from Mexico. In this note, Meteorus arizonensis Muesebeck is recorded for the first time for the country, obtained from the fall armyworm, Spodoptera frugiperda (J.E. Smith), with materialfrom Santa Maria del Oro, locality in the State of Nayarit.